Approximation of general α-cubic functional equations in 2-Banach spaces - Eskandani, G. Z.; Rassias, J. M. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We introduce a new α -cubic functional equation and investigate the generalized Hyers – Ulam stability of this functional equation in 2-Banach spaces.